Islamic Social Enterprise Framework: The Case Of Malaysia - Nurul Aini Muhamed; Nathasa Mazna Ramli; Syadiyah Abdul Shukor; Nur Syazwani Mohamed Nasrudin (Kyoto University, 2024)
Non-Indexed Publication